2015
DOI: 10.1007/s13197-014-1673-3
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of process conditions for Rohu fish in curry medium in retortable pouches using instrumental and sensory characteristics

Abstract: 'Kalia', a popular preparation of Rohu fish, packed in four-layered laminated retort pouch was processed in a steam/air mixture over-pressure retort at 121.1°C to three different F 0 values of 7, 8 and 9 min. Time-temperature data were collected during heat processing using an Ellab Sterilization Monitoring System. Texture profile such as hardness, springiness, gumminess and chewiness decreased as the F 0 value increased. The L* values decreased whereas a* and b* values increased with increasing F 0 value. Bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 24 publications
(31 reference statements)
1
13
0
1
Order By: Relevance
“…Many studies are reported in the literature about the thermal processing of seafood and fish in retort pouches (Byun et al, 2010;Kuda et al, 2008), e.g., mackerel (Gopal et al, 2001;Simpson et al, 2004), tuna , shrimp (Mohan et al, 2008;Mallick et al, 2010), anchovy (Bindu et al, 2010), Rohu fish (Majumdar et al, 2015), etc. Giustino TRIBUZI 1 However, only few studies were found about thermal processing of bivalve molluscs.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies are reported in the literature about the thermal processing of seafood and fish in retort pouches (Byun et al, 2010;Kuda et al, 2008), e.g., mackerel (Gopal et al, 2001;Simpson et al, 2004), tuna , shrimp (Mohan et al, 2008;Mallick et al, 2010), anchovy (Bindu et al, 2010), Rohu fish (Majumdar et al, 2015), etc. Giustino TRIBUZI 1 However, only few studies were found about thermal processing of bivalve molluscs.…”
Section: Introductionmentioning
confidence: 99%
“…The heating rate index was faster in curry medium by steam-air retort than in curry medium processed by water immersion application. Earlier reports were observed heating rate index of 18 min for jewfish paste Thankamma et al (1998) and the same values were observed in mackerel curry , 25 -32 min for seer fish curry Ravishankar et al (2002), 19 min for shrimp kuruma Mohan et al (2006), 19 -23.30 min for prawn kuruma Mohan et al (2008), 13 -18 min for fish peera from anchovy Bindu et al (2010), 18.60 to 24.50 min for rohu curry at different F 0 values Majumdar et al (2015), 17.50 min for tilapia sandwich paste Dhanapal et al (2016), 28.19 min for rohu balls curry Majumdar et al (2017), 10.50 -11.71 min for eel steaks in brine, Mugale et al (2018a) and 8.88 -10.15 min for eel curry Mugale et al (2018b). In most of the above studies, heating rate index values were within the range of 8.88 to 32 min.…”
Section: Heating Rate Indexmentioning
confidence: 62%
“…Similarly, Dhanapal et al, (2010) observed the sensory scores for tilapia fish paste processed for different F 0 values i.e. 6, 7, 8 and 9 min, Abhilash et al, (2013) observed the sensory score of crab koftha processed for different F 0 values of 5, 6 and 7 min and sensory score for rohu curry processed for different F 0 values of 7, 8 and 9 as observed by Majumdar et al, (2015).…”
Section: Sensory Analysismentioning
confidence: 82%
“…1) respectively. These decreasing trends of texture profiles were mainly due to the increase in the heat treatment (Majumdar et al, 2015). Sreenath et al, (2008) noted the decreasing in texture profile of shrimp curry processed for different F 0 values at 121 o C. Majumdar et al, (2015) observed the decreasing trend in texture profile of rohu curry processed at 121.1 o C. Mohan et al, (2006) reported the decreasing trend in texture profile of 'Shrimp Kuruma' in retort pouch and aluminium cans.…”
Section: Texture Profile Analysismentioning
confidence: 97%